Parliamentary behaviour of the opposition Pakatan Rakyat in Malaysian politics, 2008-2012 / Ariff Aizuddin Azlan - Ariff Aizuddin, Azlan (2017)
This study examines the patterns of parliamentary behaviour of Pakatan Rakyat (PR) political parties in the Twelfth Parliament. The study is based upon two significance arguments: first, the opposition Pakatan Rakyat political parties (PAS, PKR, and DAP) for the first time collectively work as a single political force in the Twelfth Parliament; and second, the patterns of behaviour would likely trigger some responses and constraints from the ruling Barisan Nasional (BN) government and at the same time would consolidate the oppositional coalition politically. The 2008 Malaysia‟s general election was held under very pressurized circumstances. Unfortunately, the election result indicated that the ruling BN was no longer politically durable and thus provided a new political vacuum for the opposition PR to emerge as part of national political alternatives. This is a qualitative study and therefore it will adopt the approach of “content analysis” as a research technique. The data were collected from primary sources such as parliamentary debates (Hansards), government official documents, party‟s publications, interviews, and newspapers. As the secondary sources, books and articles were used. By using Shane Martin‟s Framework of Parliamentary and Legislative Behaviour, the study reveals that there are several PR patterns of behaviour evident in the 12th Parliament. These main and sub-patterns were manifested in the form of parliamentary struggle and were perceived as a counter-measure to the policies of the ruling BN government. Besides that, the study found that the parliamentary constraints encountered by PR have led towards the consolidation of patterns of behaviour in the Twelfth Parliament. Finally, this study concluded that the parliamentary behaviour of Pakatan Rakyat has strengthened, empowered and consolidated the practice of oppositional parliamentary democracy and the emergence of the newly coined-term known as the “New Parliamentary Behaviour (NPB)”.